2009
DOI: 10.1177/0165551509104231
|View full text |Cite
|
Sign up to set email alerts
|

A relational data harmonization approach to XML

Abstract: There are numerous approaches for integrating data from heterogeneous data sources. A common background assumption is that the data sources remain quite stable and are known in advance. Hence an integration system can be built to manipulate them. In practice there is, however, often a demand for supporting ad hoc information needs concerning unexpected autonomous data sources containing volatile data. A different approach is therefore needed. We propose that semantically similar data are harmonized when extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 31 publications
(77 reference statements)
0
31
0
Order By: Relevance
“…In particular they propose SLCA [41] and MLCA [25] whose general intuition is that the LCA must be minimal. However, in [28,32] they showed that these approaches still produced undesired combinations between data items in some cases (e.g. when a data item needs to be combined with a data item at a lower level of the document hierarchy).…”
Section: Related Workmentioning
confidence: 99%
“…In particular they propose SLCA [41] and MLCA [25] whose general intuition is that the LCA must be minimal. However, in [28,32] they showed that these approaches still produced undesired combinations between data items in some cases (e.g. when a data item needs to be combined with a data item at a lower level of the document hierarchy).…”
Section: Related Workmentioning
confidence: 99%
“…In other words, we can assume that the most of the existing data sources can be represented based on XML, which can, in turn, be represented unambiguously as XML relations. This affords us the possibility to utilize the data harmonization approach introduced in Niemi et al (2009).…”
Section: Related Work 21 Xml and Relational Databasesmentioning
confidence: 99%
“…As discussed in our previous work (Niemi et al, 2009), in many advanced applications, such as online analytical processing (OLAP), this kind of query language is necessary to satisfy the ad hoc information needs of the user. In that context, we also demonstrated formally that the XML relation representation and the related constructor algebra can be used to resolve all kinds of data conflict types in data harmonization.…”
Section: Ijwis 71mentioning
confidence: 99%
See 2 more Smart Citations